A microscopic study of power management in IEEE 802.11 wireless networks. (23rd February 2007) - Hu, Chunyu; Zheng, Rong; Hou, Jennifer C.; Sha, Lui
In this paper, we demonstrate via a rigorous, analytical model that the periodic structure in IEEE 802.11 Power-Save Mode (PSM) together with its signalling overhead leads to both energy and bandwidth under-utilisation. We then devise Sleep In the Middle and Prolonged Activeness (SIMPA), a new power management protocol based on IEEE 802.11 PSM, to decouple the power management decision points and the Beacon Intervals (BIs), so as to allow fine grained control. In SIMPA, wireless devices can switch to the sleep state inside a BI or extend their active states beyond one BI. A comprehensive simulation study in both single hop wireless LANs without the AP support and multihop wireless networks demonstrates that as compared to IEEE 802.11 PSM, SIMPA can effectively reduce energy consumed under light to medium traffic loads and retain the network capacity for data transport at high traffic loads.